Mineralisasi Emas di Kalisat, Magelang, Jawa Tengah: Prospek Emas Tipe Epitermal Sulfidasi Rendah di Pegunungan Kulon Progo -Menoreh - Idrus, Arifudin (2014)
Study area is located in Kalisat and its vicinity, Magelang district, situated at the northern part of Menoreh-Kulon Progo mountain range. This study is aimed to characterize the hydrotermal alteration and ore mineralogy, ore chemistry and geological features of the gold mineralization in order to interpret the styles of gold deposit style.